Combined Effects of Estrogen and Mechanical Loading on Anterior Cruciate Ligament Fibroblast Biosynthesis - Xuhui Liu; Zong-Ping Luo (The Scientific World Journal)
For some time, estrogen has been suspected to play a negative role in anterior cruciate ligament (ACL) fibroblast biosynthesis; however, reports on this issue have been controversial. In a recent study, our group demonstrated a negative combined effect of estrogen and mechanical loading on the gene expression of major extracellular matrix component molecules in ACL fibroblasts.